ANALISIS YURIDIS KOMPARISI PENGHADAP DALAM AKTA NOTARIS BERDASARKAN STUDI PUTUSAN NO.51PK/TUN/2013 - META PERMATA SARI (PREMISE LAW JURNAL, 2016)
Personal Appearance comes from the word ‘Comparant” which has broader meaning i.e. it does not only refer to the act of appearing, but also regarding identity of the person appearing. Analyzing personal appearing is important in order that whenever there is any misquote or mistyped in the personal appearing writing, caused by Notary’s carelessness or indirectly caused by other people who do not give true statement that influence the deed and all parties as well as the Notary are authorized and going to be responsible civilly and criminally. Therefore, it is interesting to analyze these problems; how to make personal appearance an authentic deed in a notarial deed, how about Notary’s liability for personal appearance error in a notarial deed reviewed from the Ruling No.51/PK/TUN/2013, and what efforts should be made by a notary in order to prevent such error in making person appearance in a notarial deed. This was a judicial normative research which applied prescriptive approach. The data collection was obtained from library study. Based on the research done, it was figured that personal appearance of an authentic deed consists of identities. Positions refers to act for one self or as an authority or its holder according to the power of attorney and various representative. Based on the case No. 51PK/TUN/2013, the Notary was administratively sentenced for violating the stipulation in Article 85 of UUJN (Laws on Notary’s Position) and a Notary must perform his/her duty in accordance with the principles of Notary’s. Keywords: Personal Appearance, Person Appearing, Notarial Deed